1995
DOI: 10.1139/v95-117
|View full text |Cite
|
Sign up to set email alerts
|

Aryldiazenido complexes: structure, fluxionality, and properties of the iridium ethylene aryldiazenido complex [(η5-C5Me5)Ir(C2H4)(p-N2C6H4OMe)][BF4] and a comparison with the analogous nitrosyl complex [(η5-C5Me5)Ir(C2H4)(NO)][BF4]

Abstract: [Cp*Ir(C2H4)(N2Ar)][BF4] (1BF4; Ar = p-N2C6H4OMe) has been synthesized by reacting [ArN2] [BF4] with Cp*Ir(C2H4)2 at low temperature. An initial electrophilic attack of the incoming diazonium ion at iridium, followed by expulsion of C2H4, is postulated to account for the mild reaction conditions that are in sharp contrast to the usual inertness of the bis(ethylene) compound toward ligand substitution. The IR and nitrogen NMR data for 1BF4 and its 15Nα derivative unambiguously establish that the ArN2 ligand has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…[24,25] In these cases, Au III species bearing an aryldiazenide ligand (ArN 2 À )h ave been proposed as the key intermediates that undergo the photoelimination of N 2 ,b ut they were not isolated. Arenediazoniums are also known to oxidatively add to complexes of several metal ions, including Ru II , [30] Ir I [31] or Pd II , [32] to give aryldiazenidec omplexes. As far as we are aware,t here is only one report describing the oxidative addition of an arenediazonium to aP t II species, which gives al abile aryldiazenide Pt IV complex that easily undergoes N 2 elimination.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] In these cases, Au III species bearing an aryldiazenide ligand (ArN 2 À )h ave been proposed as the key intermediates that undergo the photoelimination of N 2 ,b ut they were not isolated. Arenediazoniums are also known to oxidatively add to complexes of several metal ions, including Ru II , [30] Ir I [31] or Pd II , [32] to give aryldiazenidec omplexes. As far as we are aware,t here is only one report describing the oxidative addition of an arenediazonium to aP t II species, which gives al abile aryldiazenide Pt IV complex that easily undergoes N 2 elimination.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier paper of this series we reported that the singly-bent aryldiazenido ligand , bound in an end-on coordination fashion ( I ), has unique anisotropic π electronic properties 4a. It has strong π-accepting ability only in the bending plane, whereas in the perpendicular direction it is a moderate π-donor.…”
Section: Introductionmentioning
confidence: 99%
“…Of key importance is an understanding of the geometric and electronic requirements of the differently coordinated aryldiazenido ligands in complexes. Some effort has been made to obtain a general theoretical description of the electronic structure of the bonding in transition metal organodiazenido complexes. 4a However, little is known about how the molecular geometry, the properties of ancillary ligands, or, importantly, the geometrical disposition of the ancillary ligand in a given molecular geometry influence the metal−aryldiazenido bonding. We have been concerned with these questions, both in the experimental arena and in the theoretical domain.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the aryl ring may, in principle, be directed syn to either of the ligands L 1 or L 2 . Furthermore, when the ligands L 1 and L 2 differ in their π donor−acceptor properties, the d orbital is rotated and the plane of the aryldiazenido ligand therefore is also rotated, so that now the CN···ReL 1 dihedral angle is near 90° (where L 1 is the better π acceptor) as in Scheme . ,
1 (a) Idealized Conformers of [Cp*ReL 1 L 2 (N 2 Ar)] + That Arise from the Two Possible Orientations of the Aryldiazenido Ligand. (b) Diagram To Show the Important Overlap of the Filled Rhenium d π Orbital with the Empty In-Plane Nitrogen p Orbital
…”
Section: Introductionmentioning
confidence: 99%